A2DLT : Divisible Load Balancing Model for scheduling communication-intensive grid applications. - Othman, Mohamed; Abdullah, M.; Ibrahim, Hamidah; Subramaniam, Shamala (Springer-Verlag Berlin Heidelberg, 2008)
Scheduling an application in data grid is significantly complex and very challenging because of its heterogeneous in nature of the grid system. Divisible Load Theory (DLT) is a powerful model for modelling data-intensive grid problem where both communication and computation loads are partitionable. This paper presents a new divisible load balancing model known as adaptive ADLT (A2DLT) for scheduling the communication intensive grid applications. This model reduces the maximum completion time (makespan) as compared to the ADLT and Constraint DLT (CDLT) models. Experimental results showed that the model can balance the load efficiently, especially when the communication-intensive applications are considered.